2021
DOI: 10.1111/aos.14953
|View full text |Cite
|
Sign up to set email alerts
|

Autologous versus allogeneic versus umbilical cord sera for the treatment of severe dry eye disease: a double‐blind randomized clinical trial

Abstract: To measure the effects of Autologous serum (AS), Allogeneic Serum (HS) and Umbilical Cord serum (CS) eye drops in severe dry eye disease (DES), as well as to characterize and quantify several molecules in the three sera (albumin, fibronectin; Vitamin A and E; IgG, IgA and IgM; Transforming growth factor β; Epithelial growth factor).Methods: Randomized, double-blind, single-centre, three-arm (AS, HS and CS) clinical trial. Sixty-three subjects were included with severe DES, 21 in each arm of the study. Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…[9] Many clinical randomized controlled trials have been reported, exploring many drugs and therapies for the treatment of autoimmune diseases. Intramuscular injection of ianalumab (VAY736), shown to be effective and safe [10] ; Autologous versus allogeneic versus umbilical cord sera has obvious effect on severe dry eye [11] ; LD-IL-2 was effective and well tolerated in patients with pSS, and it restored immune balance, with enhanced regulatory T cells and CD24highCD27 + B cells. [12] However, there are no high-quality reviews of advances in disease treatment, and the field urgently needs high-quality review articles.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Many clinical randomized controlled trials have been reported, exploring many drugs and therapies for the treatment of autoimmune diseases. Intramuscular injection of ianalumab (VAY736), shown to be effective and safe [10] ; Autologous versus allogeneic versus umbilical cord sera has obvious effect on severe dry eye [11] ; LD-IL-2 was effective and well tolerated in patients with pSS, and it restored immune balance, with enhanced regulatory T cells and CD24highCD27 + B cells. [12] However, there are no high-quality reviews of advances in disease treatment, and the field urgently needs high-quality review articles.…”
Section: Resultsmentioning
confidence: 99%
“…Allo-SED was preferred to auto-SED in view of similar efficacy and better logistic organization, as it is made using previously stored blood, with subsequent quicker and more convenient production. 8 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of SED, both allogenic (allo-SED) and autologous (auto-SED), has been well proved in case of dry eye associated with SS, while the literature regarding the efficacy of contact lens is manly based on no-SS-associated dry eye, with only few studies reporting the results of standard bandage contact lenses and scleral contact lens in patient with SS. 6 , 7 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…90 As yet, there are only 4 RCTs on limited number of severe DED patients, which comparatively evaluated the efficacy of allo-PBS versus other serum eye drops, with equivocal results. [85][86][87][88] Umbilical Cord Blood Serum…”
Section: Allogenic Peripheral Blood Serum (Allo-pbs) Dropsmentioning
confidence: 99%